Digital transformation in the banking industry: Empirical lessons from leading Vietnamese banks - Tuan, Tran Viet; Huyen, Nguyen Thi Thanh; Duong, Doan Nhat (Edelweiss Applied Science and Technology, 2026)
In the context of the digital era reshaping the global economy, this study aims to clarify the nature and trajectory of digital transformation in four major Vietnamese banks, Techcombank, Vietcombank, VPBank, and BIDV, as microcosms of an emerging economy. The research pursues three objectives: (i) to analyze digital transformation strategies and implementation approaches; (ii) to evaluate the impact of digital technologies on operational efficiency, competitive capability, and customer experience; and (iii) to draw lessons for developing countries transitioning toward a digital economy. The study is grounded in Vial’s [1] digital transformation framework, complemented by Chesbrough’s [2] open innovation perspective, together with digital maturity models and Rogers’ [3] innovation diffusion theory. A qualitative research design combining multiple case studies is employed, using data from secondary sources and semi-structured interviews. The collected data are analyzed through thematic analysis to examine strategic, organizational, and technological dimensions of digital transformation. The findings reveal that digital transformation in Vietnamese banks extends beyond technology adoption to include organizational restructuring, process reconfiguration, and customer-centric innovation. Banks that effectively align technological investments with organizational capabilities demonstrate stronger improvements in operational performance and customer experience, providing practical insights for financial institutions and policymakers in emerging economies.